Labor's Flaming Youth: Telephone Operators and Worker Militancy 1878-1923 - Bernard, Elaine (Labour / Le Travail, 1991)
The article reviews the book, "Labor's Flaming Youth: Telephone Operators and Worker Militancy 1878-1923," by Stephen H. Norwood.
Keywords: BOOKS – Reviews; LABOR'S Flaming Youth: Telephone Operators & Worker Militancy 1878-1923 (Book); NORWOOD; Stephen H.; Nonfiction; Radicalism